2011
DOI: 10.5688/ajpe756109
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Empathy in Pharmacy Students

Abstract: Objective. To validate the Jefferson Scale of Empathy-Health Profession Students version (JSE-HPS) in pharmacy students. Methods. The JSE-HPS (20 items), adapted from the original Jefferson Scale of Empathy for use among students in the healthcare professions, was completed by 187 first-year pharmacy students at Midwestern University Chicago College of Pharmacy. Results. Two factors, "perspective-taking" and "compassionate care," emerged from factor analysis in this study, accounting for 31% and 8% of the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
146
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(168 citation statements)
references
References 35 publications
16
146
3
3
Order By: Relevance
“…19,20 JSE-HPS has long been recognised as a validated instrument for empathy studies in pharmacy education, and was believed appropriate for the assessment of educational outcomes of different programs to enhance empathy and research on correlates of empathy in pharmacy education and practice. 9 The original Jefferson Scale of Physician Empathy (JSPE) developed nearly a decade ago has been widely used to measure empathy in physicians and medical students around the world, including a recent report on Chinese medical students. 20 However, JSE-HPS revised from the original JSPE was first used in a study of undergraduate nursing students in 2011, 25 which provided support for the validity and reliability of JSE-HPS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19,20 JSE-HPS has long been recognised as a validated instrument for empathy studies in pharmacy education, and was believed appropriate for the assessment of educational outcomes of different programs to enhance empathy and research on correlates of empathy in pharmacy education and practice. 9 The original Jefferson Scale of Physician Empathy (JSPE) developed nearly a decade ago has been widely used to measure empathy in physicians and medical students around the world, including a recent report on Chinese medical students. 20 However, JSE-HPS revised from the original JSPE was first used in a study of undergraduate nursing students in 2011, 25 which provided support for the validity and reliability of JSE-HPS.…”
Section: Discussionmentioning
confidence: 99%
“…Two researches have been reported about the measurement properties of the JSE-HPS among pharmacy students. 9 firstly examined the validity and reliability of the JSE-HPS in 187 first-year pharmacy students at Midwestern University Chicago College of Pharmacy. 19 then showed that scores on the empathy scale were positively associated with JSE-HPS scores in 158 American pharmacy students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations